Children's Rights in Islamic Law: A Contemporary Study of Family Practices - Siti Nurjanah; Ahmad Syarifudin; Muhammad Mujib Baidhowi; Elva Mahmudi; Hidayat Darussalam (Faculty of Sharia, IAIN Metro, 2025)
Children are creatures created by God that must be protected and maintained with honor and dignity. The fulfillment of children's rights is an interesting issue to discuss. This study aims to analyze the fulfillment of children's rights in the family from the perspective of Fiqh and analyze effective ways that must be done so that the guarantee of the fulfillment of children's rights can be realized properly. This study uses a literature review. The data collection technique used is documentation, which examines scientific journals, books, and documents related to the research object. The analysis method used in this study is the Miles and Huberman analysis method. The data validation technique used is source triangulation, which compares one source with another source so that the data obtained is valid. An important finding in this study is the fulfillment of children's rights if narrowed down more deeply into five things: the fulfillment of rights related to religious affairs (Hifz al-din), the fulfillment of rights related to the soul (Hifz al-nafs), the fulfillment of rights related to honor and nasab (Hifz al-Nasl), the fulfillment of rights related to reason (hifz al-aql), and the fulfillment of rights related to property (Hifz al-mal). Children must be guaranteed their right to grow and develop following their nature; therefore, all forms of treatment that interfere with and damage children's rights in various forms of violence, discrimination, and exploitation that are not inclusive must be abolished without exception. The guarantee of the fulfillment of children's rights needs to be integrated with the applicable legal regulations in society to be more effective, namely Law Number 4 of 1979, Presidential Decree Number 36 of 1990, and Law Number 35 of 2014 concerning Child Protection as a form of amendment to Law Number 23 of 2002 concerning Child Protection. This study contributes to the academic discourse by offering a normative reconstruction of children's rights within the family through the lens of maqaṣid al-shari'ah, thereby integrating classical fiqh principles with contemporary child protection laws in Indonesia.